1995
DOI: 10.1126/science.7754373
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Chaperone Protein Hsp104 in Propagation of the Yeast Prion-Like Factor [ psi + ]

Abstract: The yeast non-Mendelian factor [psi+] has been suggested to be a self-modified protein analogous to mammalian prions. Here it is reported that an intermediate amount of the chaperone protein Hsp104 was required for the propagation of the [psi+] factor. Over-production or inactivation of Hsp104 caused the loss of [psi+]. These results suggest that chaperone proteins play a role in prion-like phenomena, and that a certain level of chaperone expression can cure cells of prions without affecting viability. This ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
1,120
3
4

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 988 publications
(1,162 citation statements)
references
References 29 publications
31
1,120
3
4
Order By: Relevance
“…The prion-like nature of [psi þ ] has been confirmed recently, and it has been shown that Sup35p (eRF3) molecules interact with each other through their N-terminal domains in [psi þ ] but not in [psi ¹ ] cells (Patino et al, 1996;Paushkin et al, 1996). It is proposed that Hsp104p is important in establishing the [psi þ ] inheritance (Chernoff et al, 1995). From these and other observations not discussed here it seems probable that the N-termini of eukaryotic eRF3 molecules possess functions different from those of the C-termini; in other words, eRF3 proteins should be considered multifunctional.…”
Section: The Prion-like Properties Of Erf3mentioning
confidence: 98%
“…The prion-like nature of [psi þ ] has been confirmed recently, and it has been shown that Sup35p (eRF3) molecules interact with each other through their N-terminal domains in [psi þ ] but not in [psi ¹ ] cells (Patino et al, 1996;Paushkin et al, 1996). It is proposed that Hsp104p is important in establishing the [psi þ ] inheritance (Chernoff et al, 1995). From these and other observations not discussed here it seems probable that the N-termini of eukaryotic eRF3 molecules possess functions different from those of the C-termini; in other words, eRF3 proteins should be considered multifunctional.…”
Section: The Prion-like Properties Of Erf3mentioning
confidence: 98%
“…Although several human diseases accompanied by amyloid formation are known, none of them have been reproducibly transmitted. Interestingly, two yeast phenotypes are ascribed to 'heritable protein conversion', namely the [URE3] and the [psi +] systems [73,74], opening new perspectives for the elucidation of this phenomenon.…”
Section: Implications and Outlookmentioning
confidence: 99%
“…Molecular chaperones also play a critical role in the propagation of yeast prions (10), which are examples of intracellular amyloids that, in general, are not inherently toxic (11,12). However, the conversion of active soluble Sup35 and Ure2 into their prion states [PSI ϩ ] and [URE3], respectively, inactivates these proteins (11,12).…”
mentioning
confidence: 99%
“…Yeast prion formation occurs spontaneously at a low frequency, and the prion state is then perpetuated through the templating of newly synthesized prion proteins by preexisting amyloid-like prions (13). Templated prion proteins then undergo stable changes in structure and function to enter an amyloid-like state that is propagated and passed from mother cells to their daughters in a molecular chaperone-dependent manner (10). Yeast prions thereby constitute cytoplasmically transmitted, protein-based elements of inheritance that are dominant in genetic crosses (prions are denoted by brackets, italics, and capital letters to reflect these properties).…”
mentioning
confidence: 99%